I'LAL AND IBDAL IN THE POETRY OF AHMED SHAWQI (AN ANALYTICAL MORPHOLOGICAL STUDY): AL-I'LĀL WA-AL-IBDĀL FĪ SHI'R AHMAD SHAWQĪ (DIRĀSAH TAHLĪLIYAH ṢARFIYAH) - Millah Hanifah; Fatimah Fatimah; Azhari Azhari (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
Arabic linguistics encompasses a broad range of disciplines traditionally classified into thirteen branches, including morphology and syntax as the core of grammatical studies, as well as semantics, rhetoric, prosody, rhyme, literary history, and lexicology. Among these branches, morphology occupies a central position because it examines the structural formation of Arabic words, covering original and additional letters, sound and weak letters, and their various morphological patterns. Within this field, the phenomena of iʿlāl and ibdāl are particularly important, as they function not only as morphological processes but also as aesthetic and phonological devices that support rhythmic balance in Arabic poetry. Iʿlāl refers to changes involving weak letters to meet linguistic or metrical requirements, whereas ibdāl involves the substitution of one letter for another to achieve phonetic harmony. This study aims to identify the forms of words containing iʿlāl and ibdāl in the poetry of Ahmad Shawqi and to analyze the factors that cause their occurrence as well as their effects on word formation. The research adopts a descriptive qualitative approach supported by analytical methods applied to selected poetic verses. The findings reveal several categories of iʿlāl in Shawqi’s poetry, including 30 instances of iʿlāl bi al-qalb, 5 instances of iʿlāl bi al-ḥadhf, 1 instance of iʿlāl bi al-taskīn, 2 instances of iʿlāl bi al-qalb wa al-ḥadhf, and 1 instance of iʿlāl bi al-taskīn wa al-qalb. This study is expected to contribute to the enrichment of morphological and stylistic studies in Arabic literary research.